FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN FURNITURE PADA PT SAF MITRA ABADI DI KOTA BATAM - andika, andika andika; Raymond, Raymond (SCIENTIA JOURNAL, 2021)
As we know, the development of the furniture business in Batam City in the early twenty-first century has been developing very rapidly and is still undergoing a process of continuous development. This encourages the emergence of many new types of businesses that can become one of the threats for PT Saf Mitra Abadi. PT Saf Mitra Abadi is a company engaged in the field of furniture that has been established since 2009 in Batam City. The purpose of this study is to determine whether there is an influence between promotion, service quality and product quality partially and simultaneously on consumer purchasing decisions at PT Saf Mitra Abadi. In this study, the authors used a descriptive quantitative research method using 155 populations. In this study, the authors used the Simple Random Sampling technique in determining the population used. SPSS (Statistical Product and Service Solution) version 25 is a program used by the author to process data obtained from respondents. The results in this study indicate that there is a positive and significant influence between promotion, service quality and product quality partially and simultaneously on the consumer purchasing decisions of PT Saf Mitra Abadi.